2012
DOI: 10.1245/s10434-011-2210-5
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of MRI for Assessment of T Category, Lymph Node Metastases, and Circumferential Resection Margin Involvement in Patients with Rectal Cancer: A Systematic Review and Meta-analysis

Abstract: BACKGROUND: MRI is increasingly being used for rectal cancer staging. The

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
284
6
11

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 469 publications
(335 citation statements)
references
References 89 publications
(81 reference statements)
9
284
6
11
Order By: Relevance
“…Algebally et al [14] also reported 84% sensitivity, 97% specificity and 94% accuracy. Our results are close to the results of Al-Sukhni et al [21] that were 95% specificity and 93% sensitivity.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Algebally et al [14] also reported 84% sensitivity, 97% specificity and 94% accuracy. Our results are close to the results of Al-Sukhni et al [21] that were 95% specificity and 93% sensitivity.…”
Section: Discussionsupporting
confidence: 91%
“…Tumor extension near but >1 mm distant from the circumferential resection margin is sometimes referred to as a threatened circumferential resection margin. [21] Our results showed MRI sensitivity of CRM assessment reaching 96%, specificity 94% and accuracy 96%. Algebally et al [14] also reported 84% sensitivity, 97% specificity and 94% accuracy.…”
Section: Discussionmentioning
confidence: 49%
“…37 MRI specificity was 75 % for tumor stage and 71 % for lymph node involvement. 38 A thorough workup cannot completely confirm that a tumor will be definitively treated with local excision.…”
Section: Patient Selectionmentioning
confidence: 99%
“…Further substantial progress in terms of local recurrence reduction was achieved with the advent of quality-assured total mesorectal excision (TME; [15]). The next step was the introduction of magnetic resonance imaging (MRI) as a routine preoperative staging tool [1] facilitating the visualization of the distance between tumor and mesorectal fascia. If this distance is ≥1 mm on MRI, a negative circumferential resection margin (CRM) is assumed, provided that total mesorectal excision surgery is performed adequately.…”
Section: Rectal Cancermentioning
confidence: 99%